PERMAINAN BOGABITA DAN PELATIHAN PEMBUATAN GERABAH SEBAGAI MEDIA PENGUATAN KARAKTER ANAK JALANAN DI KOMUNITAS PPAP SEROJA KOTA SURAKARTA - umi - yuliati; M. Bagus Sekar Alam; Tiwuk K. Hastuti; Warto Warto; Insiwi F. Setiasih; Isnaini W. Wardani; Sawitri P. Prabawati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
This service focuses on fostering street children under the Seroja Women's and Children's Empowerment Institute (PPAP) in Surakarta. The purpose of this activity is to help restore the condition of the children assisted by PPAP Seroja socially by developing the potential of children through character development so that they have a sense of love for the homeland and social care. This is in line with Law Number 20 of 2003 concerning the National Education System which aims to develop the potential of students to become human beings who believe and fear God, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. answer. The specific target to be achieved in this service activity is to foster a sense of love for the homeland and social care of the children assisted by PPAP Seroja through the introduction of exemplary heroes, regional culture, and local products in the form of pottery. The method used in the implementation of this activity is the method of observation, discussion, simulation or educational games with the BOGABITA Boardgame method and clay edu (introduction of pottery with printing techniques). The problem that is the background of this service activity is the condition of the children under the guidance of PPAP Seroja having difficulty socializing after the covid-19 pandemic, especially with the educational environment so that this has an impact on the soul and character of children who tend to be selfish, lack social sensitivity, especially efforts to foster a sense of love. homeland to themselves. The implementation of service activities is to hold simulations or games in stages as a means of personal, fun approach using the BOGABITA Boardgame and clay edu methods (introduction of pottery with printing techniques). The output targets for this service activity are children who understand the importance of socializing, sharing, and getting to know local and Indonesian culture more closely, seminar proceedings with ISBN, publication of service activities in print or online mass media, and publication of service in the form of videos.